Urgency of Legal Personal Data Protection in E-Commerce Transactions Involving Artificial Intelligence - Junaidi; Rozlinda Mohamed Fadzil (Universitas Islam Negeri Walisongo Semarang, 2024)
The protection of personal data has become increasingly critical in the digital era, particularly in e-commerce transactions involving the use of Artificial Intelligence (AI). A significant legal gap persists because, although Indonesia has enacted Law No. 27 of 2022 on Personal Data Protection, there are still no implementing regulations specifically addressing the use of AI in personal data collection and processing. Consequently, legal protection for consumers remains inadequate and vulnerable to misuse by digital businesses and cybercriminals. This study aims to analyze the effectiveness of legal protection for consumers’ personal data in Indonesia and to assess the urgency of regulating AI use in e-commerce activities. The research employs a normative legal method, utilizing legislative and conceptual approaches. The findings reveal that AI can enhance the detection and prevention of personal data breaches more effectively. However, without implementing regulations and an independent supervisory authority, AI may also pose significant privacy risks. Moreover, the lack of clear legal standards governing the accountability of electronic system operators for data security further weakens personal data protection. This study recommends formulating detailed implementing regulations governing AI use in personal data management and establishing an independent supervisory body with the authority to monitor, evaluate, and enforce compliance with personal data protection laws. Perlindungan data pribadi menjadi semakin krusial di era digital, terutama dalam transaksi e-commerce yang melibatkan penggunaan Kecerdasan Buatan (Artificial Intelligence, AI). Terdapat kesenjangan hukum yang signifikan karena, meskipun Indonesia telah memberlakukan Undang-Undang No. 27 Tahun 2022 tentang Perlindungan Data Pribadi, belum terdapat peraturan pelaksana yang secara spesifik mengatur penggunaan AI dalam pengumpulan dan pemrosesan data pribadi. Akibatnya, perlindungan hukum bagi konsumen masih belum optimal dan rentan terhadap penyalahgunaan oleh pelaku bisnis digital maupun kejahatan siber. Penelitian ini bertujuan untuk menganalisis efektivitas perlindungan hukum terhadap data pribadi konsumen di Indonesia serta menilai urgensi pengaturan penggunaan AI dalam aktivitas e-commerce. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan perundang-undangan dan konseptual. Hasil penelitian menunjukkan bahwa AI dapat meningkatkan efektivitas deteksi dan pencegahan kebocoran data pribadi. Namun, tanpa adanya peraturan pelaksana dan lembaga pengawas independen, AI juga berpotensi menimbulkan risiko serius terhadap privasi. Selain itu, ketiadaan standar hukum yang jelas terkait tanggung jawab penyelenggara sistem elektronik atas keamanan data semakin melemahkan perlindungan data pribadi. Penelitian ini merekomendasikan penyusunan peraturan pelaksana yang komprehensif mengenai penggunaan AI dalam pengelolaan data pribadi serta pembentukan lembaga pengawas independen yang berwenang untuk memantau, mengevaluasi, dan menegakkan kepatuhan terhadap peraturan perlindungan data pribadi.Keywords: Artificial Intelligence; E-commerce; Legal Protection; Personal Data